Cyber security threats: A never-ending challenge for e-commerce - Liu, Xiang; Ahmad, Sayed Fayaz; Anser, Muhammad Khalid; Ke, Jingying; Irshad, Muhammad; Ul-Haq, Jabbar; Abbas, Shujaat (Frontiers in Psychology, 2022)
This study explores the challenge of cyber security threats that e-commerce technology and business are facing. Technology applications for e-commerce are attracting attention from both academia and industry. It has made what was not possible before for the business community and consumers. But it did not come all alone but has brought some challenges, and cyber security challenge is one of them. Cyber security concerns have many forms, but this study focuses on social engineering, denial of services, malware, and attacks on personal data. Firms worldwide spend a lot on addressing cybersecurity issues, which grow each year. However, it seems complicated to overcome the challenge because the attackers continuously search for new vulnerabilities in humans, organizations, and technology. This paper is based on the conceptual analysis of social engineering, denial of services, malware, and attacks on personal data. We argue that implementing modern technology for e-commerce and cybersecurity issues is a never-ending game of cat and mouse. To reduce risks, reliable technology is needed, training of employees and consumer is necessary for using the technology, and a strong policy and regulation is needed at the firm and governmental level.